THE DEVELOPMENT OF A DIGITAL FLIPBOOK FOR IPAS LEARNING CONTENT BASED ON BALINESE LOCAL WISDOM TO IMPROVE LEARNING OUTCOMES OF FOURTH GRADE ELEMENTARY SCHOOL STUDENTS - Muzakki, Muhammad Fajar; Irwan Febryan; Nyoman Ayu Putri Lestari (STKIP Citra Bakti, 2026)
This research focuses on creating a digital flipbook based on Balinese local wisdom for the